Splitsville [videorecording (DVD)] - Covino, Michael; Covino, Michael; Marvin, Kyle; Marvin, Kyle; Johnson, Dakota, 1989-; Arjona, Adria, 1992-; Braun, Nicholas; Castañeda, David, 1989-; Fagbenle, O-T, 1980-; Wingo, David; Morris, Dabney; Stokes, Callan; et al. (Decal Releasing LLC, 2025)
"After Ashley asks for a divorce from good-natured Carey, he runs to friends Julie and Paul for support. He's shocked to discover their secret to happiness is an open marriage; that is, until Carey crosses the line and throws all of their lives into chaos."--